2014
DOI: 10.1038/ncomms4795
|View full text |Cite
|
Sign up to set email alerts
|

S100A11 is required for efficient plasma membrane repair and survival of invasive cancer cells

Abstract: Cell migration and invasion require increased plasma membrane dynamics and ability to navigate through dense stroma, thereby exposing plasma membrane to tremendous physical stress. Yet, it is largely unknown how metastatic cancer cells acquire an ability to cope with such stress. Here we show that S100A11, a calcium-binding protein up-regulated in a variety of metastatic cancers, is essential for efficient plasma membrane repair and survival of highly motile cancer cells. Plasma membrane injury-induced entry o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
243
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(276 citation statements)
references
References 50 publications
21
243
2
Order By: Relevance
“…[19][20][21][22][23] It is overexpressed in a large variety of invasive carcinomas, and its suppression substantially decreases cell migration. 21,23 Therefore, the reduced motility of siBC200-transfected HeLa cells could result from the BC200 RNA-knockdown-induced downregulation of S100A11. Shown are Mock-siNegative (red), Mock-siBC200 I (pale red), CBC200-siNegative (blue) and CBC200-siBC200 I (pale blue) (mean § SD; n D 3; Ã P < 0.05, by Student's ttest).…”
Section: Depletion Of Bc200 Rna Disrupts the Migration And Invasion Omentioning
confidence: 99%
See 2 more Smart Citations
“…[19][20][21][22][23] It is overexpressed in a large variety of invasive carcinomas, and its suppression substantially decreases cell migration. 21,23 Therefore, the reduced motility of siBC200-transfected HeLa cells could result from the BC200 RNA-knockdown-induced downregulation of S100A11. Shown are Mock-siNegative (red), Mock-siBC200 I (pale red), CBC200-siNegative (blue) and CBC200-siBC200 I (pale blue) (mean § SD; n D 3; Ã P < 0.05, by Student's ttest).…”
Section: Depletion Of Bc200 Rna Disrupts the Migration And Invasion Omentioning
confidence: 99%
“…Since BC200 RNA is highly expressed in some breast cancer cells [19][20][21][22][23] we also analyzed the connection between BC200 RNA, cell motility, and S100A11 expression (Fig 9). We found that the BC200 RNA knockdown decreased the wound-healing rate.…”
Section: Bc200 Rna Knockdown Decreases Cell Motility and S100a11 Exprmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] While much of the focus has been on disease resulting from poor PMR, we have recently identified that improved PMR is an important contributor for cancer metastasis. 13 Human breast cancer cells that turn metastatic through Keywords: actin, annexins, Annexin A2, breast cancer, cancer, plasma membrane repair, S100 proteins, S100A11, Metastasis up-regulation of truncated EGF receptor (ErbB2) also need to up-regulate their PMR machinery, and absence of enhanced PMR compromises their invasive ability. Here we will briefly discuss the mechanisms involved in PMR, with a focus on the involvement of annexins, actin and S100 proteins.…”
Section: Introductionmentioning
confidence: 99%
“…We recently identified this to be the case, as PM of invasive cancer cells suffered greater damage. 13 In response, we find these invasive cancer cells enhance their PMR by up regulating expression of S100A11 and annexin A2 proteins. 13 Annexins and S100 proteins are commonly up regulated in variety of cancers.…”
mentioning
confidence: 99%